Acute and Posttraumatic Stress in Family Members of Children With a Prolonged Stay in a PICU: Secondary Analysis of a Randomized Trial. Issue 4 (22nd February 2022) - Erçin-Swearinger, Hazal; Lindhorst, Taryn; Curtis, J. Randall; Starks, Helene; Doorenbos, Ardith Z.
Abstract : OBJECTIVES: To identify the prevalence of screening criteria for acute and posttraumatic stress disorders (PTSDs) and stress symptoms among family members of children in the PICU for more than 8 days and examine risk factors for stress symptoms. DESIGN: Secondary analysis of data from a randomized trial of a palliative care intervention conducted between 2010 and 2014. SETTING: An urban pediatric hospital in Seattle, WA. SUBJECTS: The sample included 377 family members of 220 children. INTERVENTIONS: Family Communication Study. MEASUREMENTS AND MAIN RESULTS: Outcomes were symptom scores and diagnostic screening criteria for acute stress disorder (ASD) and PTSD. Predictors included demographic- and admission-related characteristics and hypothesized risk factors for developing stress-related mental health disorders. The mean score for acute stress symptoms during the ICU stay was 40.3 (sd = 13.8) and 59 family members in total met diagnostic screening criteria for ASD during hospitalization (15.6%). At 3-month follow-up, the mean score for posttraumatic stress symptoms was 30.8 (sd = 12.9) and 52 family members met diagnostic criteria for PTSD (13.8%). Factors associated with meeting ASD screening criteria were unplanned admission and poorer family relationships. Factors associated with PTSD symptoms and diagnosis were longer length of stay, meeting ASD criteria during admission, child's death, and less perceived social support. CONCLUSIONS: Meeting screening criteria for PTSD was associated with demographic, length of stay, and family relationships among family members of seriously ill children. PTSD outcomes were higher among family members whose child died. This study helps identify risk factors that can be used to target needed psychosocial screening, monitoring and support during and following a prolonged PICU admission, as well as family-centered interventions and supportive bereavement intervention for the family members of a deceased child.